Effects of the stem bark extracts of sclerocarya birrea on the activities of selected diabetic related carbohydrate metabolizing enzymes - Thovhogi, Ntevheleni (University of Limpopo (Medunsa Campus), 2009)
Background and Purpose The stem bark, roots and leaves of Sclerocarya birrea (S. birrea), {(A. Rich) Hochst}, subspecies caffra (Sond) Kokwaro are widely used in South Africa and some African countries as folk medicine in the treatment and management of a variety of human ailments, including diabetes mellitus. Although the blood glucose lowering effect of the stem bark extract of S. birrea have been confirmed using experimental animal models of diabetes, there is no clear understanding of the mechanism(s) whereby S. birrea stem bark extracts and/or their components exert their blood glucose lowering effects. The primary aim of the current study was to study the in vitro inhibitory effects of S. birrea stem bark extracts on the activities of selected diabetic related carbohydrate metabolizing enzymes (α-amylase, α-glucosidase and glucose 6-phosphatase). The current study also investigated the acute in vivo effect of S. birrea stem bark acetone extract on postprandial blood glucose levels after oral sucrose loading as well as the effect of S. birrea stem bark aqueous extract on hepatic glucose 6-phosphatase activity. In addition, the long term (21 days) effects of S. birrea stem bark acetone extract on fasting blood glucose levels, plasma insulin levels, plasma triglyceride and body weight in normal and alloxan induced diabetic rats were also investigated. Methods For in vitro studies: Crude hexane, acetone, methanolic and aqueous extracts of the stem bark extract of S. birrea were prepared by means of a sequential solvent extraction procedure and screened for inhibitory activities against human urinary α-amylase, rat pancreatic α-amylase, Bacillus stearothermophilus α-glucosidase and rabbit liver glucose 6-phosphatase using standard procedures for assaying the activities of these enzymes. IC50 values and mode of inhibition of extracts demonstrating appreciable inhibitory activity against α-amylase and α-glucosidase were determined and compared with those of acarbose, a known inhibitor of these two enzymes. The IC50 value and mode of inhibition of extracts demonstrating appreciable inhibitory activity against glucose 6-phosphatase were determined and compared with those of sodium orthovavadate and sodium tungstate, known inhibitors of glucose 6-phosphatase. In vivo studies: In vivo studies were conducted in normal and alloxan induced diabetic male WKY rats. Diabetes was induced in rats that had been fasted for 12 h by a single intraperitoneal injection of 140 mg/kg body weight of alloxan monohydrate freshly dissolved in sterile normal saline. The effect of S. birrea stem bark acetone extract on postprandial blood glucose level was determined in 18 h fasted diabetic and normal rats by administering orally, the plant extract (300 mg/kg) 30 minutes before an oral sucrose loading and measuring postprandial blood glucose levels after sucrose loading by means of a MediSense’s Optimum Xceed Glucometer (MOXG). In addition, rat intestinal dissacharidase (α-glucosidase/sucrase) activity was determined in homogenate of small intestine of rats sacrificed one hour after given orally either plant extract or acarbose. The in vivo effect of S. birrea stem bark extract on glucose 6-phosphatase was determined by measuring the activity of hepatic glucose 6-phosphatase at the end of the study. For the determination of the long term (chronic) effect of S. birrea stem bark crude acetone extract on blood glucose levels, body weight and water intake, alloxan induced diabetic and normal WKY rats were treated daily with S. birrea stem bark crude acetone extract (300 mg/kg) for 21 days. Fasting blood glucose levels and changes in body weight were determined on day 0, 7, 14 and 21 after initiation of treatment by means of a MOXG and gravimetrically respectively. Water intake was determined on the same days that blood glucose levels were determined by measuring the amount of water left overnight by each rat and subtracting this amount from the initial amount water given to each rat. Blood was also collected at the end of the study for the measurement of plasma glucose, triglyceride and insulin levels. Plasma glucose and plasma triglyceride levels were measured using commercially available kits based respectively on the glucose oxidase and the glycerol blanked methods (Beckman Coulter®’s UniCell DXC 800 Synchron® Clinical System). Plasma insulin levels were determined by means of an enzyme linked immunosorbant assay (ELISA) adapted to the Beckman Coulter® Ireland Inc’s UniCell DXI 800 Access® Immunoassay System. Results In vitro studies: The crude methanolic and acetone S. birrea stem bark extracts strongly inhibited both human urinary α-amylase and rat pancreatic α-amylase in a competitive manner. The inhibitory effect of the crude methanolic extract on both enzymes was significantly stronger than acarbose. Hexane and acetone crude extracts of the stem-bark of S. birrea demonstrated the highest percentage inhibition against B. stearothermophilus α-glucosidase. The mode of inhibition of the crude hexane extract on B. stearothermophilus α-glucosidase appeared to be a noncompetitive one. However, the this plant extract appeared to be a less potent inhibitor of α-glucosidase enzyme than acarbose. Rabbit liver glucose 6-phophatase was strongly inhibited by the crude aqueous S, birrea stem bark extract in a competitive manner. In vivo studies: Administration of S birrea stem bark acetone extract 30 min before oral sucrose loading significantly suppressed (P < 0.01) the rise in postprandial blood glucose levels in treated rats compared to control rats. The crude extract also decreased significantly the intestinal disaccharidase activity of experimental rats compared to control rats. These observations suggest that the in vitro inhibitory effects of the crude hexane extract on α-glucosidase enzymes are applicable in vivo Daily, continuous oral treatment of alloxan–induced diabetic and normal WKY rats with S. birrea stem bark extract for 3 weeks resulted in significant reductions in fasting blood glucose levels and water intake of treated diabetic rats compared with diabetic controls. The extract, however, failed to bring about any significant change in the body weight, plasma insulin levels, plasma triglyceride levels and hepatic glucose 6-phosphatase of treated diabetic rats compared to diabetic control rats Conclusions The results of the current study suggest that the observed in vitro inhibitory effect of S. birrea stem bark acetone extract on alpha glucosidase enzymes are applicable in vivo whereas the observed in vitro inhibitory effect of S. birrea stem bark aqueous extract on glucose 6-phosphatase are not applicable in vivo. Furthermore, in the current study S. birrea stem bark acetone extract appears to lower blood glucose levels of alloxan induced diabetic rats without increasing their plasma insulin levels. Thus, it can be concluded on the basis of the current study that S. birrea stem bark acetone and hexane extracts exert their blood glucose lowering effect in alloxan induced diabetic rats in part, through inhibition of intestinal brush border α-glucosidase enzymes.
Thesis (MSc (Biochemistry))--University of Limpopo (Medunsa Campus), 2009.
Keywords: Stem bark extracts; Sclerocarya birrea; Diabetic mellitus